Capital City Relocation: A Comparison of the Social Impacts of Putrajaya Malaysia and Nusantara Indonesia - Yumasdaleni; Syafuan Rozi; Otto Trengginas Setiawan; Fauzan Anyasfika; Nor Suzylah Sohaimi (Jurnal Lemhannas RI, 2025)
Purpose: This study discusses how capital city relocation influences society through a comparison of Putrajaya in Malaysia and IKN in Indonesia. Study Design/Methodology/Approach: TThe study uses qualitative approach and critical literature review supported by field observations and interview with community leaders, residents, and government officials in East Kalimantan. The secondary data consist of policy papers, academic publications and media reports. Findings: Although Putrajaya has successfully transformed into a modern administrative centre, however there is ongoing social issues like evictions, livelihood erosion, and weakened community cohesion. In contrast, IKN settlement is still in process but has potential risks of land conflicts and socio-economic disparities. Originality/Value: The novelty of this study lies in comparing the cases of Indonesia and Malaysia to demonstrate how strengthening Tri Gatra through land security and spatial planning, and strengthening Panca Gatra through socio-political governance, can form the basis for a capital city relocation policy that is just, inclusive, and in line with national resilience.